Bibliography on the genus Chilo Zincken (Lepidoptera: Pyralidae). - Katiyar, R. N. (Contributions to Entomology = Beiträge zur Entomologie, 1964)
There is presented a bibliography on taxonomy, bionomics, and control measures of the Pyralid genus Chilo Zincken the species of which are widely distributed (S.E. Asia, Africa, southern USA) as a well known insect pest of rice, maize, Sorghum, and sugar-cane.